Absorbent Stable Sets - Itzhak Gilboa; Dov Samet (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
This paper suggests a general framework to deal with learning, dynamics and evolution in games and economic environments. In this general set-up we define a (set-valued) solution concept and prove some properties, including existence. We then discuss more specific dynamical processes and show that the general solution concept provides quite intuitive results for various contexts.
Keywords: 330